Implementasi Pendidikan Islam dalam Membangun Kecerdasan Holistik - Maghfirotus S, Firda; Nurhidayati, Titin; Zahro Hidayati, Ainun; Rofi'ah, Nur; Titarini, Titarini (Journal of Islamic Education and Pedagogy, 2026)
Intelligence is a blessing from Allah SWT that distinguishes one human being from another. In Islam, intelligence is not limited to intellectual abilities but also encompasses spiritual, emotional, and moral dimensions. Islam positions intelligence as a means to know Allah SWT, understand His creation, and fulfill the responsibility of being a khalifah on earth. The Qur’an and Hadith emphasize the role of the intellect (‘aql) as the vessel of intelligence that enables humans to discern, restrain themselves, and make wise decisions. This paper employs a literature review method, examining various relevant scholarly sources with the aim of exploring the concept of intelligence in Islam, its types, and its role in Islamic education. Through this understanding, it is hoped that individuals with strong faith, knowledge, and noble character can be nurtured. Intellectual insight that is not accompanied by an understanding of Islamic perspectives on intelligence may easily be influenced by other paradigms of intelligence that may not align with Islamic values.